Substrate topography: A valuable in vitro tool, but a clinical red herring for in vivo tenogenesis. (November 2015) - English, Andrew; Azeem, Ayesha; Spanoudes, Kyriakos; Jones, Eleanor; Tripathi, Bhawana; Basu, Nandita; McNamara, Karrina; Tofail, Syed A.M.; Rooney, Niall; Riley, Graham; O'Riordan, Alan; Cross, Graham; et al.
Graphical abstract: Abstract: Controlling the cell–substrate interactions at the bio-interface is becoming an inherent element in the design of implantable devices. Modulation of cellular adhesion in vitro, through topographical cues, is a well-documented process that offers control over subsequent cellular functions. However, it is still unclear whether surface topography can be translated into a clinically functional response in vivo at the tissue/device interface. Herein, we demonstrated that anisotropic substrates with a groove depth of ∼317 nm and ∼1988 nm promoted human tenocyte alignment parallel to the underlying topography in vitro . However, the rigid poly(lactic-co-glycolic acid) substrates used in this study upregulated the expression of chondrogenic and osteogenic genes, indicating possible tenocyte trans-differentiation. Of significant importance is that none of the topographies assessed (∼37 nm, ∼317 nm and ∼1988 nm groove depth) induced extracellular matrix orientation parallel to the substrate orientation in a rat patellar tendon model. These data indicate that two-dimensional imprinting technologies are useful tools for in vitro cell phenotype maintenance, rather than for organised neotissue formation in vivo, should multifactorial approaches that consider both surface topography and substrate rigidity be established. Statement of Significance: Herein, we ventured to assess the influence of parallel groves, ranging from nano- to micro-level, on tenocytes response in vitro and on host response using a tendon and a subcutaneous model. In vitro analysis indicates that anisotropically ordered micro-scale grooves, as opposed to nano-scale grooves, maintain physiological cell morphology. The rather rigid PLGA substrates appeared to induce trans-differentiation towards chondrogenic and/or steogenic lineage, as evidence by TILDA gene analysis. In vivo data in both tendon and subcutaneous models indicate that none of the substrates induced bidirectional host cell and tissue growth. Collective, these observations indicate that two-dimensional imprinting technologies are useful tools for in vitro cell phenotype maintenance, rather than for directional neotissue formation, should multifactorial approaches that consider both surface topography and substrate rigidity be established.